Baseline Serum Prolactin in Drug-naive, First-episode Schizophrenia and Outcome at Five Years: Is it a Predictive Factor? - Shrivastava, Amresh (Matrix Medical Communications, 2012)
Objective: Serum prolactin is influenced by antipsychotic use but its relationships with psychopathology and general functioning are not clear. This study aimed to assess these relationships. Design: Serum prolactin levels were measured in patients with schizophrenia before being treated with antipsychotics and at various follow-up points. Setting: The study was conducted in a nongovernmental psychiatric treatment center in Mumbai, India. Participants: The participants included 30 male and 30 female drug-naïve patients with schizophrenia and 31 control participants. Measurements: The severity of psychopathology at baseline, three weeks, six weeks, and five years following treatment was assessed using a modified Brief Psychiatric Rating Scale. The Global Assessment of Functioning questionnaire was used at baseline and five years follow up. Results: Contrary to our hypotheses, prolactin levels in male but not female patients at baseline were twice those of control volunteers. Correlations between prolactin, Brief Psychiatric Rating Scale, and Global Assessment of Functioning measurements were not significant for any time point up to six weeks, but were only significant at the five-year follow-up appointments, indicating that those patients with higher levels of serum prolactin had a better outcome at five years. Conclusion: Baseline serum prolactin levels in drug-naive patients with schizophrenia may be used for long-term prognosis, but are not reliable indicators of psychopathology and prognosis in the short term. Future research is needed to conclude with confidence whether or not prolactin can be used as a biomarker of psychopathological and overall functioning in schizophrenia.